Assessment of Cardiovascular Risk Factors in Women Having Female Pattern Hair Loss - Damini Verma; Vibhu Mendiratta; Taru Garg; Smita Tripathi; Shaili Tomer (Indian Journal of Dermatology)
Background: Many studies have associated male androgenetic alopecia with the risk of cardiovascular disorders but very few studies have addressed this association in women with FPHL. Materials and Methods: This was a cross-sectional hospital-based study in which a total of 50 women (18-45 years) were recruited. The objective was to measure carotid intima-media thickness (CIMT) by doppler ultrasound, Body mass index (BMI), waist circumference, lipid profile, fasting blood sugar (FBS), insulin, testosterone, Sex hormone binding globulin (SHBG), hs-CRP, ESR and fibrinogen, in pre-menopausal women having FPHL and to correlate these parameters with severity of FPHL. The prevalence of Metabolic syndrome (MetS) and Insulin resistance were evaluated. Results: Metabolic syndrome and insulin resistance were found in 12 (24%) and 17 (34%) cases respectively. Hypercholesterolemia, elevated LDL levels and hypertriglyceridemia, low HDL levels and hyperinsulinemia were found in 11 (22%), 31 (62%), 9 (18%), 17 (34%) and 7 (14%) cases respectively. 8 (16%) cases were diabetics. Elevated ESR, increased fibrinogen levels and elevated hs-CRP were found in 43 (86%), 10 (20%) and 21 (42%) cases respectively. CIMT was found to be within its normal range. Correlation of CIMT, anthropometric indices (BMI and WC), biochemical markers (serum cholesterol, triglycerides, FBS, and fibrinogen), and presence of metabolic syndrome with severity of FPHL in terms of Ludwig grade was found to be statistically significant. Conclusions: The determination of metabolic syndrome, insulin resistance and acute phase reactants such as hs-CRP and fibrinogen may be useful screening methods to detect increased cardiovascular risk in women with FPHL.